Magnetically Insulated Line Oscillator (MILO) performance study and its parameter optimization - Dwivedi S.; Jain P.K. (My University, 2025)
A magnetically insulated line oscillator (MILO), consisting of discs-loaded coaxial cylindrical waveguide as its RF interaction structure, is field analyzed for the beam-wave interaction using linearized-Vlasov equation. We have made a sensitivity analysis and proposed a method to optimize the device structure for its beam parameters, structure parameters, and its subassemblies using field analysis and particle-in-cell (PIC) simulations. In this paper, a MILO device is analyzed for its designed value of 600 kV of dc beam voltage and 35 kA of beam current. The analysis predicts 1.0-GW RF output power, 60-J energy, and ∼6% of overall efficiency of the device for the typical design parameters. The parametric analysis has been also made, which indicates the sensitivity of the various RF structure parameters on the device performance in terms of RF power output, temporal growth rate, quality factor, and released RF energy. Through optimization, the device parameters are fixed for the device design purposes. Analytically optimized results of the RF interaction structure have been validated using a commercial PIC simulation code, MAGIC, and is found to be in agreement with analytical ∼5%}$. The optimized S-band MILO structure provides the RF power output of 1-2 GW and energy 80-100 J. We hope that the present study will be of use to MILO designers in optimizing its structure parameters, keeping the structure losses within the desired limit. © 2013 IEEE.